2014
DOI: 10.1007/s13277-014-2889-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the role of 8-OHdG and oxidative stress in papillary thyroid carcinoma

Abstract: The aim of this study was to determine levels of serum 8-hydroxy-2'-deoxyguanosine (8-OHdG) as an indicator of oxidant-induced DNA damage and oxidant status in patients with papillary thyroid carcinoma before and after surgery. This study included 25 patients with papillary thyroid carcinoma and age-matched 27 healthy controls. Total antioxidant status (TAS), total oxidant status (TOS), lipid hydroperoxide (LOOH), and 8-OHdG levels were measured. 8-OHdG levels were significantly higher in the preoperative papi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 29 publications
1
16
1
1
Order By: Relevance
“…The level of 8-OHdG can be used for estimating oxidative DNA damage. Previous studies have demonstrated that 8-OHdG level increases in many diseases, such as diabetes, cancer, and cardiovascular diseases (15)(16)(17). Our study showed that plasma 8-OHdG levels were elevated in AECOPD patients compared with those in stable COPD and healthy subjects, but no statistical difference was found between stable COPD patients and heathy subjects.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The level of 8-OHdG can be used for estimating oxidative DNA damage. Previous studies have demonstrated that 8-OHdG level increases in many diseases, such as diabetes, cancer, and cardiovascular diseases (15)(16)(17). Our study showed that plasma 8-OHdG levels were elevated in AECOPD patients compared with those in stable COPD and healthy subjects, but no statistical difference was found between stable COPD patients and heathy subjects.…”
Section: Discussioncontrasting
confidence: 53%
“…It is one of the most frequently used biomarkers for evaluating oxidative stress. Previous studies have observed elevated 8-OHdG in diabetes, cancer, cardiovascular diseases, and stable COPD (15)(16)(17). However, the level of 8-OHdG in AECOPD is still unclear.…”
Section: Introductionmentioning
confidence: 95%
“…The well developed vascularization of the thyroid clears the thyroid tissue of free radicals and deposits them into circulation, which is the probable reason why previous studies found increased serum oxidant concentrations. In addition, the potential influence of confounding factors for oxidative stress, such as smoking status and co-morbidities, on TOS and TAS values were not evaluated in previous studies (Wang et al 2011;Tabur et al 2015). Based on the present results, we propose that future studies should carry out further characterization of oxidant/ antioxidant status in PTC and BG tissues by assaying the specific enzymatic and non-enzymatic components of the redox system.…”
Section: Discussionmentioning
confidence: 68%
“…Damaging effect in thyroid tissue occur when there is the regulation misbalance between the produced free radicals and antioxidants, leading to apoptosis via activation of apoptosis signal-regulating kinase 1 (ASK1) (Du et al 2010). Papillary carcinogenesis is associated with increased serum levels of oxidants induced by the DNA damage adduct 8-hydroxy-2′-deoxyguanosine (8-OHdG), which remains high after surgery (Tabur et al 2015). Oxidative stress can be experimentally characterized by assaying numerous enzymatic and non-enzymatic compounds that contribute to the cell's redox status.…”
Section: Discussionmentioning
confidence: 99%
“…A correlação entre Pb-s e o aumento GST já foi descrita em outros estudos envolvendo exposição ocupacional ao Pb (CONTERATO et al, 2013;DOBRAKOWSKI et al, 2016) Um dos alvos das EROs são os ácidos nucleicos e, por este motivo, os ensaios que avaliam a oxidação de DNA através de 8-OHdG urinária têm sido empregados como ferramentas úteis em estudos de exposição a xenobióticos (CHANG et al, 2011;PRASAD et al, 2013;LI et al, 2014). O interesse crescente na dosagem deste biomarcador se deve à conhecida relação entre a oxidação de DNA e os processos de envelhecimento (SIOMEK et al, 2007;RADAK;BOLDOGH, 2010) e carcinogênese (PYLVÄS et al, 2011;TABUR et al, 2015).…”
Section: O Estresse Oxidativo é Um Dos Efeitos Tóxicos Mais Relevanteunclassified